1978
DOI: 10.1099/0022-1317-40-1-175
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Seroepidemiological Studies on the Human Syncytial Virus

Abstract: SUMMARYThe seroepidemiology of the human syncytial virus was investigated by means of an indirect immunofluorescence test on 24I sera from Kenya, Tunisia, Singapore and Britain. These included sera from patients with nasopharyngeal carcinoma, other tumours of the oro-nasopharynx, tumours of other parts of the body, and from normal donors. In this study, the virus was found to infect only Kenyan Africans and all but one of these seropositive subjects had tumours, particularly of the oro-nasopharyngeal spaces. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 1 publication
2
14
1
1
Order By: Relevance
“…An early seroepidemiological report had indicated that whereas 17% of Kenyan Africans had antibodies to HSV, sera from three other countries (Tunisia, Singapore, and Great Britain) were negative [9]. In contrast to the preceding study, two other studies of human sera, which included 70 from Africa, reported the absence of antibodies to the agent [6].…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…An early seroepidemiological report had indicated that whereas 17% of Kenyan Africans had antibodies to HSV, sera from three other countries (Tunisia, Singapore, and Great Britain) were negative [9]. In contrast to the preceding study, two other studies of human sera, which included 70 from Africa, reported the absence of antibodies to the agent [6].…”
Section: Discussioncontrasting
confidence: 39%
“…At the present time little is known con cerning the role of HSV in human disease. In the study on the Kenyan Africans, where a substantial incidence (17%) of positive anti body reactivity was reported, it is of particular significance to note that most of these positive reactions were seen in patients with tumors [9]. Furthermore, although HSV was originally isolated from cultures of a human NPC, it was found that those with NPC showed no greater evidence of infection (24%) than did patients with other tumors of the oronasopharynx (25%).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Early seroepidemiological studies suggested that HFV infection is common in East Africa (Kenya and Uganda) and some Pacific islands and rare in regions of North Africa (Tunisia), North America, and Britain (3,290,347). However, this was disputed by Brown and colleagues (74,75), who failed to detect markers of HFV infection in people from any of these areas.…”
Section: Human Foamy Virusmentioning
confidence: 83%